Changing patterns of teacher education - Raggett, Michael; Clarkson, Malcolm (London : Falmer Press : Ward Lock, 2012)
The Brighton Conference in 1975 was devoted to an examination of some of the problems arising from the re-organisation of teacher education in a period of economic stringency and widespread cuts in education. The book is divided into four sections. The first considers the structural changes resulting from mergers and changing institutional roles. The second considers the changing curriculum; the third consists of discussion papers by three principals of colleges of higher education and the fourth section summarises discussions and seeks to identify some future trends in teacher education.
Includes bibliographies.
Keywords: Teachers -- Training of -- Great Britain